Complication rates and management in sentinel lymph node biopsy for endometrial cancer: a retrospective cohort study - Yang, Jing; Wu, Ping; Liu, Huimin (Frontiers in Medicine, 2026)
BackgroundSystematic pelvic lymph node dissection (PLND) is the conventional staging procedure for early-stage endometrial cancer but is associated with substantial morbidity, particularly lower-limb lymphedema. Sentinel lymph node biopsy (SLNB) is a less invasive alternative, yet real-world evidence on complications and patient-reported quality of life (QoL) remains limited.ObjectiveTo compare perioperative outcomes, postoperative complications, and QoL between SLNB and PLND in low- to intermediate-risk endometrial cancer, and to determine whether surgical approach is an independent risk factor for complications.MethodsWe retrospectively analyzed 150 eligible patients with early-stage endometrial cancer treated at a gynecologic oncology center between January 2020 and December 2023, with ≥12 months of follow-up. Based on contemporaneously documented clinical decision-making and patient preference, patients were assigned to the SLNB group (n = 100) or the PLND group (n = 50). SLNB was performed using cervical indocyanine green injection with near-infrared fluorescence imaging; PLND comprised systematic pelvic lymphadenectomy. Outcomes included operative time, estimated blood loss, length of hospital stay, overall complications graded by Clavien–Dindo, 12-month lymphedema incidence, SLN mapping success rate, lymph node pathology (including ultrastaging), and QoL assessed by the EORTC QLQ-C30 preoperatively and at 3, 6, and 12 months. Univariate and multivariate logistic regression analyses were conducted to identify independent risk factors for postoperative complications.ResultsBaseline characteristics (age, BMI, FIGO stage) were comparable between groups (all p > 0.05). Compared with PLND, SLNB was associated with shorter operative time (p < 0.001), lower blood loss (p < 0.001), and shorter postoperative hospital stay (p = 0.001). The patient-level SLN mapping success rate was 97.0%. Overall complication rates (p < 0.001) and 12-month lymphedema incidence (p < 0.001) were significantly lower in the SLNB group. Ultrastaging detected six additional cases of micrometastases or isolated tumor cells in the SLNB group (p = 0.016). Global health status scores were higher after SLNB at 3 months (p = 0.007) and 6 months (p = 0.041). In multivariate analysis adjusting for age, BMI, diabetes, and FIGO stage, PLND remained an independent risk factor for postoperative complications (aOR 4.732; 95% CI 2.029–11.034; p < 0.001).ConclusionIn low- to intermediate-risk early-stage endometrial cancer, SLNB provides effective staging with reduced surgical burden, fewer postoperative complications—particularly lymphedema—and earlier recovery of QoL compared with systematic PLND.